Rodent population dynamics and crop loss estimation due to rodent pests in finger millet based crop lands : Rodent pests in finger millet based crop lands - Naik, Mohan I Naik; Binny, Vipin Chaudhary; Basavadarshan A V (Annals of Arid Zone, 2023)
Ragi (Eleusine coracana Gaertn ) also known as finger millet is an important millet widely grown in Asia and is the major staple food in southern Karnataka. Rodents are critical vertebrate pests and are regarded as big chaos to agricultural production. In the present studies the rodent population and crop loss due to rodent pest in finger millet crop was analyzed during the year 2022. The studies revealed that with mean trap index of 20.28 the rodent activity in the finger millet crop lands was observed throughout the year and the peak rodent activity was recorded in Kharif and Rabi crop seasons and was less in the dry (summer) seasons. The population was male and adult dominant with a male female ratio of 1:0.92 and adult infant ratio of 1:0.56, respectively. The Shannon index (Hǀ) in finger millet crop lands found to be 1.08 and the peak Shannon index was recorded in the month of August with a highest relative abundance of Bandicota bengalensis, Tatera indica and Mus platythrix rodent species in the finger millet crop lands. The yield loss estimation studies indicated that there was a grain loss of 2.98 q ha-1 in finger millet crop lands with a monetary value of Rs. 10, 662 (US $129.48) per hectare.